Die rol van psigiatrie in die bantering van en navorsing oor gesinsmoord - Roos, J. L. (Koers, 1992)
Very little research has been done on the phenomenon of family murders in the Republic of South Africa. In this article reference is made to the descriptive, qualitative and exploratory study of family murders, which was carried out by the HSRC. Psychiatric factors involved in family murders considered in the HSCR study are presented and the role of psychiatry at a primary, secondary and tertiary level of prevention is discussed. In conclusion suggestions are made regarding the future role of psychiatry in research relating to family murders.